Association between alcohol consumption and risk of hyperuricaemia among adults: a large cross-sectional study in Chongqing, China - Bin Peng; Xiaojun Tang; Siyu Chen; Liling Chen; Xianbin Ding; Qinwen Luo; Meng Xiao; Rui Ding (BMJ Open)
Objective To investigate the relationship between alcohol consumption and hyperuricaemia (HUA), we conducted a study based on a large population.Setting Cross-sectional study.Participants A total of 20 833 participants aged 30–79 years were enrolled in the China Multi-Ethnic Cohort, Chongqing region.Outcomes The serum level of uric acid, fasting blood glucose and blood lipids were tested. Basic demographic statistics such as age, gender, marital status, education level, family annual income and the detail information of alcohol consumption were collected using a standardised questionnaire.Results After controlling for potential confounders, compared with participants who never consumed alcohol, participants who drank 3–5 days per week had the highest risk of HUA (OR: 1.51, 95% CI: 1.25 to 1.82) and those who drank alcohol harmfully had the highest risk of HUA (OR: 1.81, 95% CI: 1.41 to 2.32). In addition, we found that those who drank moderately had no significant association with risk of HUA. However, among men, compared with participants who never consumed alcohol, those who drank moderately was also a risk factor of HUA (OR: 1.23, 95% CI: 1.03 to 1.46) and those who drank alcohol harmfully had the highest risk of HUA (OR: 2.13, 95% CI: 1.64 to 2.78). Compared with participants who drank alcohol moderately, the OR (95% CI) for those who drank alcohol harmfully had the highest risk of HUA was 1.88 (1.42 to 2.48), and the corresponding OR (95% CI) for each level increment in the degree of alcohol consumption was 1.22 (1.12 to 1.33). Among men, compared with participants who drank alcohol moderately, those who drank alcohol harmfully had the highest risk of HUA (OR: 1.93, 95% CI: 1.45 to 2.57), as well as the corresponding OR (95% CI) for each level increment in the degree of alcohol consumption was 1.24 (1.13 to 1.35).Conclusion This study suggested that the frequency and degree of alcohol consumption may be the risk factors for HUA, especially in males.